Theory of singlet fission in carotenoid dimers - Barford, W; Chambers, CA (American Institute of Physics, 2023)
We develop a theory of singlet fission in carotenoid dimers. Following photoexcitation of the “bright” state (i.e., a singlet electron–hole pair) in a single carotenoid, the first step in the singlet fission process is ultrafast intramolecular conversion into the highly correlated “dark” (or 2Ag) state. This state has both entangled singlet triplet-pair and charge-transfer character. Our theory is predicated on the assumption that it is the singlet triplet-pair component of the “dark” state that undergoes bimolecular singlet fission. We use valence bond theory to develop a minimal two-chain model of the triplet-pair states. The single and double chain triplet-pair spectra are described, as this helps explain the dynamics and the equilibrated populations. We simulate the dynamics of the initial entangled pair state using the quantum Liouville equation, including both spin-conserving and spin-nonconserving dephasing processes. By computing the intrachain and interchain singlet, triplet, and quintet triplet-pair populations, we show that singlet fission critically depends on the interchain coupling and the driving potential (that determines endothermic vs exothermic fission).